The Use of Objects of Intellectual Property as Mortgage Tools - E. V. Altukhova (Вестник Российского экономического университета имени Г. В. Плеханова)
Present day economy is based on knowledge and intellect, where the principle element of competitiveness is intellectual property. Availability of intellectual property market is an integral part of the innovation economy development, which determines the form and procedure of objects of intellectual property circulation. In industrialized countries intellectual property becomes a factor of production. The necessity to use objects of intellectual property in economic relations is stipulated also by globalization processes taking place in economy. It is impossible to realize the Strategy of Scientific and Technological Development of the Russian Federation without new technologies. At the same time the development, protection and introduction of new technologies are not feasible without new approaches and methods of using objects of intellectual property in the system of economic relations. One of these approaches is the use of intellectual property as a mortgage tool. The article analyzes a possibility of using objects of intellectual property as a mortgage. It studies practice and features of such deals in Russia and abroad. Legislative regulation of these relations is also investigated. Key conditions of the credit deal using object of intellectual property as a mortgage were formulated, the principle criterion of conducting this transaction is the use of the effective object of intellectual property, which can guarantee min risks both for the creditor and the borrower.